2009
DOI: 10.1083/jcb.200807176
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial degeneration and not apoptosis is the primary cause of embryonic lethality in ceramide transfer protein mutant mice

Abstract: Ceramide transfer protein (CERT) functions in the transfer of ceramide from the endoplasmic reticulum (ER) to the Golgi. In this study, we show that CERT is an essential gene for mouse development and embryonic survival and, quite strikingly, is critical for mitochondrial integrity. CERT mutant embryos accumulate ceramide in the ER but also mislocalize ceramide to the mitochondria, compromising their function. Cells in mutant embryos show abnormal dilation of the ER and degenerating mitochondria. These subcell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 69 publications
1
101
0
1
Order By: Relevance
“…There was considerable controversy concerning the role of SLs in mitochondria function (47), but recent studies measuring SL levels both in isolated mitochondria (48) and on isolation of enzymes of SL metabolism from mitochondria (49 -52) have suggested that SLs are involved in regulation of mitochondrial function. This is supported by the involvement of the mitochondrial pathway in the pathology of a CERT-knock-out mouse (53). Unfortunately, no tools are available to determine the precise subcellular (or suborganellar) localization of long or very long chain ceramides.…”
Section: Discussionmentioning
confidence: 98%
“…There was considerable controversy concerning the role of SLs in mitochondria function (47), but recent studies measuring SL levels both in isolated mitochondria (48) and on isolation of enzymes of SL metabolism from mitochondria (49 -52) have suggested that SLs are involved in regulation of mitochondrial function. This is supported by the involvement of the mitochondrial pathway in the pathology of a CERT-knock-out mouse (53). Unfortunately, no tools are available to determine the precise subcellular (or suborganellar) localization of long or very long chain ceramides.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, ER-like membranes associated with isolated mitochondria appear to produce enough ceramides to allow transient penetration of the outer membrane by pro-apoptotic proteins (Stiban et al, 2008). However, the actual contribution of mitochondrial ceramides to the apoptotic response in living cells is a topic of controversy (Ségui et al, 2006;Wang et al, 2009;Chipuk et al, 2012). Resolving this issue is challenging because ceramides are readily metabolized into various other bioactive lipid species, which can influence the sensitivity of cells to apoptosis through multiple pathways (Hait et al, 2006;Hannun and Obeid, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In mutants lacking Cer kinase, the resulting Cer accumulation alters phosphatidylinositol biphosphate (PIP 2 ) membrane distribution, leading to loss of phospholipase C activity and consequent failure in phototransduction, accompanied by severe degeneration of photoreceptors; overexpression of ceramidase in these mutants leads to Cer decrease and rescues PLC activity ( 145 ). Mouse embryos lacking Cer transport protein (CERT), which transfers Cer from the ER to the Golgi, accumulate Cer in mitochondria in cells from the optic cup and this accumulation alters mitochondria structure ( 146 ). These results underscore the signifi cance of controlling Cer levels to regulate membrane processes and thus prevent the death of retina photoreceptors.…”
Section: Ceramide In the Retinamentioning
confidence: 99%